Analgesia strategy for inguinal hernia repair in children: a systematic review and network meta-analysis of randomized clinical trials based on regional blocks - Xue, Xing; Zhou, Yuxin; Yu, Na; Yang, Zhihua (Frontiers in Pediatrics, 2024)
Background and objective: Despite its acknowledged benefits, the selection of an optimal regional block for analgesia pediatric hernia surgery remains a subject of debate. This study endeavored to conduct a network meta-analysis and systematic review of randomized clinical trials, aiming to amalgamate insights from both direct and indirect comparisons concerning the analgesic effectiveness and safety of various regional blocks post-inguinal hernia repair in children.Method: A comprehensive literature search was performed across PubMed, EMBASE, Web of Science, and the Cochrane Library up to 12 November 2022 by two independent reviewers, employing a standardized protocol. The inclusion criteria encompassed randomized trials focusing on children undergoing inguinal hernia repair utilizing either local infiltration analgesia or regional analgesia. The primary outcomes assessed were pain scores at 2, 6, and 24 hours post-operation.The initial search yielded 281 records relating to 1137 patients. The analysis of ranking probability indicated that Paravertebral Block (PVB) holds the highest likelihood (88% and 48%) of being the most effective in alleviating pain at 2 hours and 6 hours post-surgery. Transversus Abdominis Plane Block (TAPB) emerged as the superior choice for mitigating pain (83%) and decreasing morphine consumption (93%) at 24 hours following the operation. Local Anesthetic Infiltration (LAI) was identified as the most effective in shortening the hospital stay, with a 90% probability. Conclusions: Regional anesthesia significantly enhances postoperative pain management in pediatric inguinal hernia repair surgery. For short-term postoperative pain relief, PVB emerges as the most effective technique. Meanwhile, TAPB provides more prolonged analgesia. Although TAPB does not exhibit a pronounced advantage in short-term analgesia, its simplicity and the absence of a need for a special position render it a viable option. However, the interpretation of these results should be approached with caution due to the presence of limited data and heterogeneity.